2003
DOI: 10.1111/j.1744-618x.2003.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Experienced and Less‐Experienced Nurses Diagnostic Reasoning: Implications for Fostering Students' Critical Thinking

Abstract: Standardized nursing diagnoses may cut short the time needed to develop representational thinking and spare cognitive reserves for reasoning needed for complex patients. Faculty need to promote student's cognitive development through strategies that promote active, reflective, and integrative learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…However, other studies show that experts do not use hypothetico-deductive process of reasoning (Patel et al 2001c). It has further been shown that experienced nurses in medical-surgical units use heuristics rather than guidelines to rapidly and accurately form initial impressions of new patients (Simmons et al 2003;Ferrario 2003). Similar effects take hold in triage, where it has been recognized that less experienced nurses look for textbook signs and symptoms to reach their diagnosis, whereas more experienced nurses base their decision on specific pieces of information provided by the patient as well as their past experiences (Cioffi 1998).…”
Section: Nurse Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, other studies show that experts do not use hypothetico-deductive process of reasoning (Patel et al 2001c). It has further been shown that experienced nurses in medical-surgical units use heuristics rather than guidelines to rapidly and accurately form initial impressions of new patients (Simmons et al 2003;Ferrario 2003). Similar effects take hold in triage, where it has been recognized that less experienced nurses look for textbook signs and symptoms to reach their diagnosis, whereas more experienced nurses base their decision on specific pieces of information provided by the patient as well as their past experiences (Cioffi 1998).…”
Section: Nurse Factorsmentioning
confidence: 93%
“…Research has shown that experienced nurses make decisions more efficiently than less experienced nurses (e.g., Marsden 1998;Ferrario 2003). In triage, experienced nurses are able to quickly determine the most appropriate triage category whereas the inexperienced nurses take their time individually assessing every piece of data, not knowing what the optimal triage category will be until the very last step of their evaluation; an inherently less efficient process.…”
Section: Triage Nursing Training and Educationmentioning
confidence: 98%
“…In addition, the possibilities within human behavior and ways to help people improve their health are so numerous for nurses (1,147 concepts) that nurses are not likely to recall the most appropriate concepts. The availability of SNLs decreases nurses' cognitive demand (Ferrario, 2003) and makes it possible to select the terms that best apply in a particular situation so that high quality care can be achieved and communicated.…”
Section: Improved Quality and Patient Safetymentioning
confidence: 99%
“…The standout concept stemming from all of the literature on remote robotics in health care [25,28,29] is that the technology has great potential in improving the clinical reasoning skills of health-care professionals allowing the clinician to practice a task and skill in a risk free environment, developing confidence and building competence [17,30,31].…”
Section: B Nursing and Ralmentioning
confidence: 99%